Reinvestment: Examining convergent, discriminant, and criterion validity using psychometric and behavioral measures. (May 2015) - Laborde, Sylvain; Musculus, Lisa; Kalicinski, Michael; Klämpfl, Martin K.; Kinrade, Noel P.; Lobinger, Babett H.
Highlights: Intuitive people have a lower reinvestment tendency. Reinvestment is linked to self-consciousness, rumination, and perfectionism. Visual search performance of high reinvestors more disrupted under pressure. Older participants have a lower reinvestment score. Reinvestment is associated with higher motor imagery ability. Abstract: Given scarce external validity available to date concerning the reinvestment construct, the aim of this four-study research project was to further explore the validity of the Movement-Specific Reinvestment Scale and the Decision-Specific Reinvestment Scale, using psychometric and behavioral measures. Study 1 showed that deliberative participants had a higher reinvestment tendency than intuitive participants. Study 2 showed that reinvestment was linked to self-consciousness, rumination, perfectionism, and had satisfactory test–retest reliability. Moreover, it provided some potential insights on the development of reinvestment due to parental criticisms. Study 3 indicated that high decision reinvestors performed worse than their low decision reinvestor counterparts in a visual search task under pressure. Study 4 showed that older participants had a lower reinvestment score, and that reinvestment was associated with higher motor imagery ability, challenging the idea that reinvestment can only be seen as detrimental to performance.